The Effectiveness of Solution-focused Narrative Therapy and Mindfulness-based Stress Reduction on the Level of Expressed Emotion in Mothers of Boys With Gross Motor Disabilities - Behnaz Karami; Anahita Khodabakhshi-Koolaee; Hassan Heidari; Hossein Davoodi (Iran University of Medical Sciences, 2023)
Background: Mothers with disabled children often express emotions, such as aggression and criticism toward their children. This study aimed to compare the effectiveness of solution-focused narrative therapy (SFNT) and mindfulness-based stress reduction (MBSR) on managing the expressed emotions of mothers of boys with gross motor disabilities. Methods: This quasi-experimental study has a pre-test-post-test design with intervention and control groups. The research population consisted of all the mothers of children with gross motor disabilities referred to the "Success Counseling Center" in Tehran City, Iran, in 2022. A total of 45 eligible mothers were selected and randomly assigned to three groups: Two intervention groups and one control group (each 15). The SFNT was held in nine 90-minute sessions and the MBSR therapy in eight 90-minute sessions. The data were collected with the level of expressed emotion (LEE) scale and analyzed using descriptive statistics, such as frequency, percentage, Mean±SD, and the multivariate analysis of covariance (MANCOVA) and LSD post hoc test in SPSS software, version 26. The significance level was set at P<0.05. Results: The post-test results showed a statistically significant difference between the mean scores of expressed emotion of the three groups (P<0.05). However, compared to MBSR, SFNT demonstrated greater efficacy in reducing mothers' expressed negative emotions (P<0.05). Conclusion: Both therapies effectively reduced expressed negative emotions in mothers with disabled male children. However, SFNT had a greater effect on expressed emotion compared to MBSR. In addition to pharmacological treatments, psychological interventions (SFNT and MBSR) can help mothers of boys with gross motor disabilities manage their expressed emotions and care for their children better.